FAKTOR-FAKTOR YANG MEMPENGARUHI SISA HASIL USAHA KOPERASI DI KOTA DENPASAR - Yuliastuti, Ida Ayu Nyoman; Susandya, Anak Agung Putu Gede Bagus Arie (PIRAMIDA; Vol 14 No 1 (2018): PIRAMIDA`- Jurnal Kependudukan dan Pengembangan Sumber Daya Manusia, 2018)
Net income is one of the factors that affecting the growth of Koperasi (national micro finance business in Indonesia). Even if profit is not the main purpose of it business, but Koperasi needed to improve its business capability. This study aims to determine and analyze the effect of the number of members, owned capital, external capital, business volume and assets to the Sisa Hasil Usaha (SHU) in Denpasar. The research method used in this research is using secondary data, which is come from financial report of Koperasi in Denpasar in 2015 to 2017. The sample was 92 collected by purposive sampling technique. Data analysis technique used in this research is multiple linear regression analysis. The results showed that the variable owned capital, business volume and assets have a positive effect on the SHU. In contrast, total members and total assets were not significantly effect on SHU because they have a level of significance greater than 0.05.